2015
DOI: 10.4314/ahs.v15i3.4
|View full text |Cite
|
Sign up to set email alerts
|

Triple positivity of HBsAg, anti-HCV antibody, and HIV and their influence on CD4+ lymphocyte levels in the highly HIV infected population of Abeokuta, Nigeria

Abstract: Background: Few studies exist on hospital-based seroprevalence of triple positivity of HIV/HBV/HCV in Nigeria. Objectives: The study aimed at determining the triple positivity of HIV, HBsAg and HCV among HIV-infected individuals in Abeokuta, Nigeria and defining the influence of these triple infections on CD4+ counts of HIV-infected individuals as antiretroviral therapy improves in Nigeria. Conclusion:The study further confirms that triple positivity of HIV/HBV/HCV infection is common in Abeokuta, Nigeria. Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
11
3
Order By: Relevance
“…Contrary to some previous studies [70,71] in our cohort HCV/HBV co-infection did not have a significant influence on the natural history of HIV infection. Our findings are in accordance with the study of Kallas E. et al who also showed that HBV/HCV co-infection does not significantly affect the number of CD4 lymphocytes in patients with HIV/HBV/HCV triple infection [72].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to some previous studies [70,71] in our cohort HCV/HBV co-infection did not have a significant influence on the natural history of HIV infection. Our findings are in accordance with the study of Kallas E. et al who also showed that HBV/HCV co-infection does not significantly affect the number of CD4 lymphocytes in patients with HIV/HBV/HCV triple infection [72].…”
Section: Discussioncontrasting
confidence: 99%
“…20 Likewise, HIV infection increased the risk of rapid progression of liver-related disease in patients with chronic HBV infection. 5 , 20 , 25 , 26 The rate of acquiring chronic HBV infection among the HBV–HIV co-infected individuals and those infected with HBV alone is 25% and 4% respectively. 42 Unlike the above findings, one prospective study suggested HBV–HIV co-infected patients are less likely to develop liver disease progression than HBV mono-infected, particularly among those with non-AIDS stages.…”
Section: Impact Of Hiv On Liver Complicationmentioning
confidence: 99%
“…Hepatitis B virus and HCV infections are known to be the common cause of chronic hepatitis and leading causes of liver-related deaths [3,4]. Both HBV and HCV have been implicated in liver cirrhosis and hepatocellular carcinoma [3][4][5][6], while HIV infection has been widely established to target and decrease the CD4 + cell, a glycoprotein found abundantly on the surfaces of regulatory T cells, T-helper cells, dendritic cells, monocytes and macrophages [7].…”
Section: Introductionmentioning
confidence: 99%
“…About 3% of the world population is reported to be infected with HCV [3,4]. Many risk factors have been documented to be associated with single, double and triple co-infection of these viruses [1,5,7,9]. The natural causes of HBV and HCV infections show variability among individuals [11] and all three viruses have been identified to share common routes of transmission [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation